Drug involvement in fatal overdoses - Christopher J. Ruhm (Elsevier, 2017)
Death certificate data from the Multiple Cause of Death (MCOD) files were analyzed to better understand the drug categories most responsible for the increase in fatal overdoses occurring between 1999 and 2014. Statistical adjustment methods were used to account for the understatement in reported drug involvement occurring because death certificates frequently do not specify which drugs were involved in the deaths. The frequency of combination drug use introduced additional uncertainty and so a distinction was made between any versus exclusive drug involvement. Many results were sensitive to the starting and ending years chosen for examination. Opioid analgesics played a major role in the increased drug deaths for analysis windows starting in 1999 but other drugs, particularly heroin, became more significant for recent time periods. Combination drug use was important for all time periods and needs to be accounted for when designing policies to slow or reverse the increase in overdose deaths.